Communicative and Stylistic Potential of New Yoruba Idioms and Idiomatic Expressions on The Label of Alcoholic Drinks - Dayo Akanmu (Masyarakat Linguistik Indonesia Universitas Andalas, 2019)
This paper investigated issues expressed with these idioms as well as the strategy for using them for various modern alcoholic drinks in Yoruba land. The paper adopted Mukarovsky's theory of Standard Language based on its ability to explain the deviant nature of the new Yoruba idioms as well as explaining 'differencia specifica' between the language of everyday conversation and Literary Language. Data were collected from different beer joints in Lagos State and Ògùn State respectively as States where most of these drinks are produced. Eventually, data were subjected to stylistic analysis. In all, sex is the only issue that was expressed. Sex, which was peculiar to all the alcoholic drinks, occurred in the context of 'eroticism', 'vulgarity', 'sexual style', and 'sexual positioning'. Only the metaphorisation linguistic strategy was employed for the coining of the idioms and was differentially derived from nominalizations, phonaesthetic coinages, and compositions. Nominalisations, compositions, and phonaesthetic coinages occurred in almost all the labels, and they were contextualized in eroticism ('Ọ̀ ṣọmọ', 'Alọmọ', 'Ògidigà' and 'O ́ ríjìn (ọ rí i jìn?); sexual style (Kòbókò, Kerewa, Pakurumo) while Dadubule revealed sexual positioning. New Yorùbá idioms, used to express-socio economic and emotive issues in routine communication, occurred in mediated and non-mediated contexts and were conveyed through metaphorisations. These idioms rethe flect dynamism and modernity-constrained stylistic choices in Yorùbá discourses.